Determination of hosts of fusarium moniliforme var. subglutinans of pineapple - Aguilar, Juan Angel Espinal (Pesquisa Agropecuaria Brasileira, 2014)
The behaviour of fusarium isolates from maize, pineapple, srghum, sugarcane and millet was studied as related to their pathogenicity to pineapple slips and fruits as well as to maize and sugarcane. The isolates from maize, sorghum, sugarcane and millet were not pathogenic to pineapple slips and fruits, and it was not possible the re-isolation of the pathogen four months after the inoculation, except for the pineapple Fusarium, which was isolated from the inoculated slips and fruits. Howeve, when the Fusarium moniliforme and Fusarium moniliforme var. subglutinans were inoculated in sugarcane Stalk the pathogens were re-isolated. The results showed that all isolates were capable of causing rot in sugarcane stalk, and maize grains and stalk significantly. It became evident that F. moniliforme var. subglutinans from pineapple can survive in maize and sugarcane, and that F. moniliforme from sorghum, maize, millet and sugarcane were not pathogenic to pineapple, under this reported trial conditions.